Clinical picture, diagnosis and surgical treatment of old damages of tibiofibular syndesmosis (a review of literature) - Yaremenko, Dmytro; Yershov, Dmytro; Yaremenko, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
Anatomic-functional peculiarities of tibiofibular syndesmosis and its part in the preservation of functional stability of the ankle joint, as well as anatomic deviations in the joint in cases of neglected damages of tibiofibular syndesmosis, are analysed. Clinical, radiological and tomographic criteria for the objective assessment of the tibiofibular junction, as well as modern tendencies in surgical treatment of neglected damages of tibiofibular syndesmosis, are elucidated.